Men are from Mars: The challenges of communicating as a male nursing student. (November 2018) - Christensen, Martin; Welch, Anthony; Barr, Jennie
Abstract: Male-female communication within nursing is often fraught with difficulties especially for male nurses as the try and assimilate themselves into a female dominated profession. It is clear that men and women possess different communication styles. Men tend to be forthright and to the point. Women on the other hand often view the world as a network of connections, as a negotiation for closeness and support and therefore centred on maintaining solidarity. The aim of this study was to explore the lived-experience of a group of male nursing students using Colaizzi's seven step data analysis within the phenomenological empirical framework. The central theme "Men are from Mars" identified two subthemes which included: calling a spade a spade in world of shovels and conscientious objector from the margins. Communication for the men in this study was difficult. The participants were sensitive of what and how they communicated could be misinterpreted which often left them feeling isolated. They were often perplexed how the female students spoke to and about each. The men on the other hand were open and honest in the way they communicated with each other; there was not misinterpretation the men knew exactly where they stood with each other.